PENGARUH PENGGUNAAN TEPUNG SINGKONG DAN TEPUNG ULAT LIMBAH KELAPA SAWIT TERHADAP PENAMPILAN AYAM PEDAGING FASE STARTER - Palulungan, John Arnold (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2012)
This research aims to know the usage of cassava starch and larva palm wastes in ration of starter broiler period. A 100 of SR 707 day old chick in average body weight of 49,53Â±3,37 g reared. Those DOCs reared into 20 boxes. A completed randomized design consisted of four ration treatments, i.e. without cassava starch, and larva palm wastes, cassava starch 11.10%+ larva palm waste starch 3.60%, cassava starch 21.70%+larva palm waste starch 7.5%, and cassava starch 32.50%+larva palm waste starch 11,00%. Ration with iso-energy and protein content 22.5% and metabolic energy of 3000Kcal. Each treatment repeated five times and therefore 20 units of research obtained. Variables observed were feeding rations, growth rate, feeding ration efficiency, and mortality. The findings shown the usage of cassava starch 32.5% and larva palm waste starch with 11% can substitute cassava of 45% in starter broiler feeding ration. Substitute of cassava starch 32.5% and cassava starch of wastes of 11% is still increasing ration of consumption and daily growth rate in the starter growth period on substitution of cassava starch 2.70% and larva palm waste starch up to 7.5%. Efficiency of fed ration on treatment was not significant.